The effect of comorbidities of preeclampsia and eclampsia on maternal and fetal outcome - M. C., Abinaya; Taye, Milon K.; Saikia, Nabajyoti; Teron, Long; Kalita, Pulak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The aim of this study is to comparatively assess the maternal and fetal outcome in preeclampsia and eclampsia patients with and without comorbidities. The objectives are to assess the comorbidities associated with preeclampsia and eclampsia cases and to find out the effects of the comorbidities of preeclampsia and eclampsia on maternal and fetal outcome. Methods:380 patients who had attended antenatal OPD and emergency labour room of Assam medical college and hospital, Dibrugarh during June 2020 to July 2021 with preeclampsia and eclampsia were selected for present study. Based on relevant history, clinical and laboratory findings, these patients were further evaluated for associated comorbidities. The cases were distributed in the respective comorbidity group. Then the outcome of the mother and the baby were analyzed till the day of discharge in patients without comorbidities and with comorbidities and the same was compared. Results: The eventful maternal (44.1%) and fetal (50.92%) outcome was more in preeclampsia and eclampsia patients with comorbidities than in patients without comorbidities which is statistically significant, (p value=0.029), (p value=0.009) respectively. Conclusions: The effect of preeclampsia and eclampsia itself would adversely affect the pregnancy outcome and the effect is worse when associated with comorbidities. Appropriate prenatal counselling and optimization of the comorbidities is critical for women who are planning pregnancy.